Visual power: review of image-based methodologies and subsequent development/uses of the Fotofeedback Method™. Issue 4 (2nd October 2018) - Tornabene, Ladona; Versnik Nowak, Amy; Vogelsang, Lisa
Abstract : Over the past 60 years, image-based methodologies such as photo elicitation, photolanguage, auto-photography, hermeneutic photography, digital storytelling, photovoice and participant authored audio-visual stories have been used by qualitative researchers to better cognise humanity. Each of these methodologies are deeply rooted in visual imagery and while they may share different levels of similarities, each was coined because no existing method fully met the needs of the researchers or participants. For this same reason, a new image-based methodology, the Fotofeedback Method™ (FFM) has emerged. FFM is defined as a qualitative image-based methodology that combines participant-initiated photography with written narrative in response to a research/evaluation inquiry. This article presents an overview of FFM's formation along with examples of its use and subsequent outcomes. The aforementioned image-based methodologies are reviewed including their definition, founder, year conceptualised, discipline and location of origin, brief history, impact of use, key point and their similarities/differences to the FFM. Also presented is a comparison chart of the methodologies covered in this paper as well as a timeline of photo-based research techniques in relation to the historical development of photography, computers and social media. Current statistics regarding the power of the visual to engage others are also incorporated.